Profile Of Informal Reasoning (Ir) Of State Senior High School Students In Demak Regency - Ipah Budi Minarti; Fenny Roshayanti (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This study looks at the Informal Reasoning profiles of state high school students in the Demak Regency. Informal Reasoning is a type of thinking used by students in considering socio-scientific issues, which involves considering causation, pros and cons, and alternatives. The research was conducted at 10 state high schools in Demak Regency using the Proportionate Stratified Random Sampling method. The research data was obtained through tests in the form of multiple-choice questions and essays that tested students' mastery of Informal Reasoning regarding issues such as HIV-AIDS, GMOs, and cloning. The results showed the rational pattern with a percentage of 48.40%, the emotive pattern was 27.46%, and the lowest pattern is in the intuitive pattern with a percentage of 24.24%. Among the several factors that influence reasoning include personal experience, social considerations, which can come from educational, economic, or religious aspects, moral-ethical considerations, and their attention to technological developments as they are involved in social and technological issues, seen to be influential.